IMPACT OF RAPID WEIGHT LOSS AFTER BARIATRIC SURGERY ON LOW BACK PAIN - Dheyaa Mohammed Abdul Wahhab; Firas Fadhil Fayyadh; Saad Abdul Azeez Abdul Lateef; Younis A. Rasheed (Scholar Express Journals, 2021)
Background: Obesity raises the incidence of low back pain in overweight persons, whereas losing weight should alleviate their symptoms. However, the effects of obesity on the lumbar spine are more controversial & Despite the fact that obese people with persistent low back pain are routinely urged to reduce weight, the link between the two medical conditions is yet unknown. Aim: The goal of this study is to see the effect of rapid weight reduction on the development of LBP. Patients and Methods: a prospective study of 69 obese patients with persistent axial low back pain who were scheduled for bariatric surgery was recruited in this research during a 12-month follow up. Preoperative data was obtained; Age, height, medical comorbidities, weight, and BMI were among the demographic data collected. The Visual Analog Scale (VAS) for axial low back pain was used as an outcome measure. Follow up was done at 1, 3 and 6 months, and at 1 year following the surgery; the patients' postoperative demographic data were obtained. Results:69 patients were included in this study 23(33%) males and 46(67%) females ,all underwent bariatric surgery, the patients weights rages from 112kg to 164 kg preoperative, reduced to 89 to 132 kg, their ages range between 28 to 57 years old, their BMI (body mass index) was between 39to 54 which reduced to a range between 29 to 40, the visual analog score of the patients regarding the backache was 4 to 7 preoperative which is become 2 to 7 postoperative in a fact that 22 (31.9%) of the patients started to complain from a real backache postoperatively.36 patients (52%) get improvement in their LBP postop. , and 11 patients (15%) had no significant changes in their LBP. Conclusion: This study shows that significant weight loss following bariatric surgery can lead to significant relief of pre-existing back discomfort in nearly most of the patients & on the contrary about one third of the patients may even get worse.
Keywords: Bariatric surgery; low back ache; rapid weight loss